CONSTRUCTION DELAY ANALYSIS USING DAILY WINDOWS TECHNIQUE (Journal of Engineering, 2011)
Delays occur commonly in construction projects. Assessing the impact of delay is sometimes a contentiousissue. Several delay analysis methods are available but no one method can be universally used over another inall situations. The selection of the proper analysis method depends upon a variety of factors includinginformation available, time of analysis, capabilities of the methodology, and time, funds and effort allocated to the analysis. This paper presents computerized schedule analysis programmed that use daily windows analysis method as it recognized one of the most credible methods, and it is one of the few techniques much more likely to be accepted by courts than any other method. A simple case study has been implemented to demonstrate the accuracy and usefulness of the proposed delay analysis model. The results of the study indicate that the outcomes of delay analyses are often not predictable that each method may yield different results. The study also revealed that depending on the time and resources available, and the accessibility of project control documentation, one method may be more practical or cost-effective.